Analysis Of Leg Muscle Explosive Power Through The One Leg Triple Jump Test On 9th Grade Students Of Mts. Ar-Rahman - Sandy Suardi; Arif Hidayat; Eggi Sudjana (Athena: Physical Education and Sports Journal, 2026)
This study aims to determine the level of explosive power of leg muscles (leg muscle explosive power) MTs.Ar-Rahman Class 9 students using the testOne Leg Triple Jump(OLTJ). Explosive leg muscle power is a very important element of physical fitness, especially in sports that require strong thrust, such as the long jump and sprint.One Leg Triple JumpThis method was chosen because it effectively measures the explosive strength of the thigh and calf muscles in three consecutive jumping stages (hop, step, and jump). The research method used was descriptive quantitative with a survey technique. The research population was all 9th grade students of MTs. Ar-Rahman, with a sample of 10 students taken using the technique.purposive sampling. The research instrument used was the one-legged three-step jump test (One Leg Triple Jump Test) measured in centimeters (cm). The test data were analyzed using descriptive statistics to determine the category of leg muscle explosive power (Very Good, Good, Moderate, Less, Very Less). The results of the study showed that the average leg muscle explosive power of students was in the sufficient category. There was also an average difference between the strength of the dominant leg and the non-dominant leg. The results of the study are expected to provide an overview of the profile of students' leg muscle strength, which is useful as material for evaluating physical education teaching programs, especially in athletics material.